Empirical antimicrobial therapy of neonates with necrotizing enterocolitis: a systematic review - Donà, D; Gastaldi, A; Barbieri, E; Bonadies, L; Aluvaala, J; English, M (Thieme, 2021)
Objective Necrotizing enterocolitis (NEC) is an inflammatory disease of the gastrointestinal tract characterized by ischemic necrosis of the intestinal mucosa, mostly affecting premature neonates. Management of NEC includes medical care and surgical approaches, with supportive care and empirical antibiotic therapy recommended to avoid any disease progression. However, there is still no clear evidence-based consensus on empiric antibiotic strategies or surgical timing. This study was aimed to review the available evidence on the effectiveness and safety of different antibiotic regimens for NEC. Study Design MEDLINE, EMBASE, Cochrane CENTRAL, and CINAHL databases were systematically searched through May 31, 2020. Randomized controlled trials (RCTs) and nonrandomized interventions reporting data on predefined outcomes related to NEC treatments were included. Clinical trials were assessed using the criteria and standard methods of the Cochrane risk of bias tool for randomized trials, while the risk of bias in nonrandomized studies of interventions was evaluated using the ROBINS-I tool. The certainty in evidence of each outcome's effects was assessed using the Grading of Recommendations Assessment, Development, and Evaluation approach. Results Five studies were included in this review, two RCTs and three observational studies, for a total amount of 3,161 patients. One RCT compared the outcomes of parenteral (ampicillin plus gentamicin) and oral (gentamicin) treatment with parenteral only. Three studies (one RCT and two observational) evaluated adding anaerobic coverage to different parenteral regimens. The last observational study compared two different parenteral antibiotic combinations (ampicillin and gentamicin vs. cefotaxime and vancomycin). Conclusion No antimicrobial regimen has been shown to be superior to ampicillin and gentamicin in decreasing mortality and preventing clinical deterioration in NEC. The use of additional antibiotics providing anaerobic coverage, typically metronidazole, or use of other broad-spectrum regimens as first-line empiric therapy is not supported by the very limited current evidence. Well-conducted, appropriately sized comparative trials are needed to make evidence-based recommendations.